Community-Based Dental Education (CBDE): A Survey of Current Program Implementation at Australian Dental Schools - Millicent Taylor; Sandra Carr; Omar Kujan (International Journal of Dentistry)
Purpose. Community-based dental education (CBDE) diverges from traditional dental school training methods by integrating dental students into primary care community settings. This immersive approach enables students to refine their clinical and hands-on skills while serving the oral health needs of underserved populations. This study aimed to identify ways in which Australian dental schools are currently implementing CBDE and compared to current evidence. Materials and Methods. This study utilized a 24-item, self-completion survey, adapted from existing questionnaires, which was sent to the CBDE coordinators in the nine eligible dental programs in Australia between mid-January 2023 and mid-April 2023. The survey consisted of multiple-choice, binary, and open-ended questions, including information on the level of student involvement, types of external clinics used, length of rotations, student supervision and assessment, pre-rotation preparation, and post-rotation evaluation, as well as challenges faced in implementing programs. Results. Six of the nine invited coordinators responded, resulting in a 66.7% response rate. All participants confirmed that their schools had a community-based teaching program. All six respondents reported that participation in external clinics is required for graduation. Implementation of CBDE appears to be influenced by (1) level of student involvement, (2) the types of clinics utilised, (3) allocation and length of rotation, (4) student supervision and assessment, (5) pre-rotation preparation, and (6) post-rotation evaluation. Six (n = 6) institutions reported requiring a post-rotation reflection from students and all respondents reported seeking feedback from clinical supervisors at external sites. Emerging themes from open-ended questions highlight challenges in coordinating external rosters, securing funding, supervising students at external sites, and ensuring diverse types of student exposure during external rotations. Conclusion. This study provided insights into the implementation of CBDE in Australian dental schools. Results outlined in this research offer valuable insights for dental schools aiming to enhance their programs and improve student learning outcomes.